Strategy to Increase Political Participation of People with Disabilities Based on Functional and Contextual Approach Good Election Perspective (Study at KPU Purworejo Regency): Strategi Peningkatan Partisipasi Politik Penyandang Disabilitas Berbasis Functional and Contextual Approach Perspektif Good Election (Studi di KPU Kabupaten Purworejo) - Harum Isnin; Arif Hidayat (Faculty of Law, Universitas Negeri Semarang, 2024)
The implementation of elections in Indonesia is a manifestation of political rights for citizens, including people with disabilities as regulated in the constitution. The Regency KPU has the authority to organize elections and is responsible for providing equal opportunities for vulnerable voters with disabilities. In fact, the participation of voters with disabilities, especially the blind in Purworejo Regency, is very low. The substantial problem is the absence of SOPs for special services for the disabled and structural problems related to affirmative action have not been met. This study uses a qualitative approach with a sociological legal research type. Data collection techniques are carried out through observation, interviews, literature studies, and legal document studies. Data validity with technical triangulation and source triangulation and using descriptive analysis. The results of this study indicate that: (i) Legal provisions for political participation for blind voters with disabilities are implicitly regulated in the 1945 Constitution of the Republic of Indonesia Article 28H paragraph (2) to obtain affirmative action rights, international instruments, as regulated in the law and its ratification and the regulation of PKPU Number 9 of 2022 concerning Community Participation in Elections; and (ii) Strategies for increasing political participation for visually impaired people with disabilities in Purworejo Regency can be carried out through the formation of standard operational policies for special services for voters with disabilities based on comprehensive policies, budgeting can be carried out through financial inclusion, and special service programs based on democratic policies.